Quality of cold-pressed murici juice subjected to different concentrations of ascorbic acid - Gomes, Nayane Rosa; Soares Pierre, Bianca; Rosa de Almeida, Renato; Ascari Morgado, Cristiane Maria; Cunha Junior, Luis Carlos; de Campos, André José (Scientia Plena, 2022)
Murici (Byrsonima crassifolia (L.) Kunth) belongs to the Malpighiaceae family and is a typical fruit of the Cerrado. Its consumption occurs by local populations, both fresh and processed, such as juices, liqueurs, ice cream, jellies, yogurt, bread, and cakes. In this sense, this study aimed to assess different concentrations of ascorbic acid added to cold-pressed murici juice for the preservation of physical-chemical and bioactive characteristics. The juice was assessed for soluble solids, titratable acidity, pH, ascorbic acid and total extractable polyphenols. The experiment was conducted in a completely randomized design in a 3 × 7 factorial scheme (three concentrations of ascorbic acid × seven days of analysis) to assess three concentrations of ascorbic acid in the preservation of cold-pressed juice (0, 1, and 2%) and seven days of analysis (0, 1, 2, 3, 4, 5, and 6 days), with four replications. The data were submitted to analysis of variance (P<0.05) and, when significant, the regression analysis was performed. The concentration of 2% ascorbic acid was the most suitable for cold-pressed juice mainly because it maintains the acceptability characteristics of this product.